Melting heat transfer in hybrid nanofluid flow along a moving surface - Khashi’ie, Najiyah Safwa; Md Arifin, Norihan; Pop, Ioan; Nazar, Roslinda (Springer, 2020)
The impact and capability of Cu–Al2O3/water nanoliquid as the heat transfer fluid are numerically investigated along a moving surface with melting heat transfer. The reduced differential equations are solved and presented in the figures and tables. The percent error between present and previous numerical values is 0% which supports the model validation. The volumetric concentration of both Al2O3 and Cu nanoparticles is chosen at most 4% to avoid the instability of the nanofluid. The dual solutions are only seen when the external flow and solid surface move in an opposite direction. Remarkably, the use of hybrid nanofluid assists the boundary layer separation in the presence of melting heat transfer. However, the heat transfer rate of Cu–Al2O3/water is inevitably greater than the pure water and Cu–water. An increase in melting parameter reduces the heat transfer rate and accelerates the separation of boundary layer. The stability analysis supports the initial hypothesis from the graphical results that the second solution is unstable.